1998
DOI: 10.1046/j.1365-2842.1998.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Whiplash injuries of the temporomandibular joint in motor vehicle accidents: Speculations and facts

Abstract: Referring to the temporomandibular joint (TMJ) of the human mandibular locomotor system, it has been asserted that displacement of the TMJ disc and inflammation of TMJ tissues are the results of acute and indirect trauma to the TMJ; on occasion this is allegedly experienced in motor vehicle accidents and commonly known as a TMJ whiplash injury. It is postulated that the TMJ whiplash injury is released in the occupant or occupants of a target vehicle when its rear end is impacted by the front end of a bullet ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 72 publications
0
28
0
1
Order By: Relevance
“…During slow masticatory depression of the mandible, duration of about 236 ms (Gibbs et al, 1982;Jemt & Olsson, 1984;Karlsson & Carlsson, 1989;Karlsson et al, 1991) and an arbitrary, but probable depressor force of 3 kg, the total impulse of slow depression would be in the order of 3 ×236= 708 kg ms (1560 lb ms). In all cases, the impulses of the mandibular motion of depression are absorbed and dissipated by, primarily, the tissues of the temporomandibular joint (McKay & Christensen, 1998). Over a follow-up period of 12 months, this study found no injury to the temporomandibular joints.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…During slow masticatory depression of the mandible, duration of about 236 ms (Gibbs et al, 1982;Jemt & Olsson, 1984;Karlsson & Carlsson, 1989;Karlsson et al, 1991) and an arbitrary, but probable depressor force of 3 kg, the total impulse of slow depression would be in the order of 3 ×236= 708 kg ms (1560 lb ms). In all cases, the impulses of the mandibular motion of depression are absorbed and dissipated by, primarily, the tissues of the temporomandibular joint (McKay & Christensen, 1998). Over a follow-up period of 12 months, this study found no injury to the temporomandibular joints.…”
Section: Discussionmentioning
confidence: 56%
“…We have previously discussed the tenuous diagnosis of a so-called whiplash injury of the temporomandibular joint, and have shown that the postulated diagnosis and postulated mechanism of injury have no foundation in basic and clinical science (Christensen & McKay, 1997;McKay & Christensen, 1998, 1999. That is to say, if a rapid injurious depression of the mandible were to occur during the first phase of a whiplash manoeuvre of the head and neck (posterior rotation of the head/extension of the neck), the motion would immediately be counteracted by a mandibular elevation, elicited through a stretch reflex in the mandibular elevator muscles (Christensen & McKay, 1997), and by the inability of the rather weak depressor muscles to anchor the mandible in space (McKay & Christensen, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A so-called whiplash injury of the temporomandibular joint (TMJ) is a more than tenuous clinical concept, always postulated to be the result of a traumatic anterior acceleration of the TMJ condyles (anterior hypertranslation/posterior hyperrotation) and, usually, an ensuing traumatic posterior acceleration of the TMJ condyles (posterior hypertranslation/anterior hyperrotation). For reviews of the postulated concept and diagnosis of a TMJ whiplash injury, see Christensen & McKay (1997), Howard et al (1998) and McKay & Christensen (1998).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the emphasis is indeed on establishing functional congruency, what are the biomechanics associated with the process of heterotopic bone moving the mandible out of position? Referring to the age-old question of the relationship between whiplash and TMDs, 33,50,64,70 can bioengineers shed new light on the actual forces experienced in whiplash? More specifically, what is the significance of extension/flexion injuries of the neck and TMJ and the magnitude of condylar acceleration in these instances?…”
Section: Directives From the Clinical Communitymentioning
confidence: 99%